Advances in assembly line parts feeding policies: a literature review - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2015)
Purpose - The purpose of this paper is to present a literature review on parts feeding policies and to provide the components of parts feeding systems via a classification structure. Design/methodology/approach - This paper determines the scope and components of parts feeding systems via a classification structure under three main components such as the storage of parts, transport of parts and feeding policy. Afterward, it is focused on parts feeding policies and the related papers are reviewed and analyzed according to their feeding policy types, objectives, solution methodologies and the application types. Findings - A classification structure showing the components and scope of parts feeding systems is provided. Parts feeding policies are handled in detail and feeding policy types, objectives, solution methodologies and application types in the existing studies are presented in this paper. However, the paper highlights the open research areas and advances for academics and presents applied solution methodologies and case studies for practitioners. Originality/value - This paper reveals the scope of parts feeding systems by presenting a classification structure including three main components and related subcomponents and provides a comprehensive literature review on parts feeding policies.
Keywords: Assembly line; Feeding policy; Hybrid feeding; KITTING PROCESS; PERFORMANCE EVALUATION; OPTIMUM NUMBER; JIT PRODUCTION; SMALL-LOT; SYSTEM; DESIGN; SELECTION; KANBAN; MODEL